Persepsi Guru Terhadap Manfaat Dan Hambatan Dalam Pembelajaran Berbasis Proyek Di Sekolah Dasar - Diah Nur Fathonah (Prodi PGMI Universitas Islam Nusantara Al-Azhaar Lubuklinggau, 2025)
Project-Based Learning (PjBL) is an innovative approach aimed at developing 21st- century skills in students, such as critical thinking, creativity, collaboration, and communication. This approach provides students with the opportunity to learn through real-world projects that are relevant to their lives, bridging theory with practice. Despite its many benefits, the implementation of PjBL in elementary schools faces several challenges, such as limited time, resources, varying student abilities, and insufficient teacher training. This study aims to understand teachers' perceptions of the benefits and obstacles in the implementation of PjBL in elementary schools. The findings show that PjBL is effective in enhancing students' skills, but challenges exist in its implementation, particularly related to time management and the lack of teacher training. This study provides insights that can be used to improve the effectiveness of PjBL and support the development of educational quality in Indonesia.